2019
DOI: 10.1371/journal.pone.0217176
|View full text |Cite
|
Sign up to set email alerts
|

Declining seroprevalence of hepatitis A in Vojvodina, Serbia

Abstract: To assess the current hepatitis A virus (HAV) endemicity in the Autonomous Province of Vojvodina, Serbia, we examined the seroprevalence and susceptibility profiles of the general population. A serum bank of 3466 residual samples, collected in 2015–16 as per the specifications of the European Sero-Epidemiology Network 2 project (ESEN2), was tested for anti-HAV antibodies with an enzyme immunoassay. Relationships between anti-HAV positivity and demographic features of respondents were examined by univariable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A serosurvey conducted on samples collected in 2015–2016 showed that HAV seroprevalence in Vojvodina increased with age from 3.1% in the age group 5–9 years to 89.6% in people ≥ 60 years old [ 14 ]. By the age of 30 years, only 5% of individuals are seropositive, leaving the majority of children and young adults susceptible to HAV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A serosurvey conducted on samples collected in 2015–2016 showed that HAV seroprevalence in Vojvodina increased with age from 3.1% in the age group 5–9 years to 89.6% in people ≥ 60 years old [ 14 ]. By the age of 30 years, only 5% of individuals are seropositive, leaving the majority of children and young adults susceptible to HAV.…”
Section: Discussionmentioning
confidence: 99%
“…The Republic of Serbia is an upper–middle-income country located in central–south–eastern Europe. A previously published seroprevalence study provided evidence that HAV circulation has declined over the past four decades; thus, Serbia ranks as a very low-endemicity country nowadays, supporting the national policy of vaccination of high-risk groups [ 14 ]. National legislation opted for recommended vaccination against HA for vulnerable population groups (PID, liver transplant patients, people who work in poor hygienic conditions, and MSM) as well as for nonimmune individuals without any special risk.…”
Section: Introductionmentioning
confidence: 99%
“…It is transmitted by a fecal-oral method which happens either by direct contact with feces or indirectly by ingestion of food or water contaminated by fecal matter of the infected persons 5 . The clinical course of HAV infection is age-dependent and ranges from asymptomatic (commonly in children aged ≤ 5 years) to acute symptomatic hepatitis, with higher severity of disease in the older population 6 . The common symptoms of hepatitis infection include fever, nausea, vomiting, anorexia, general fatigue, and abdominal pain where the liver is located.…”
Section: Introductionmentioning
confidence: 99%